The role of listed real estate in multi-asset portfolio diversification: quantitative evidence from the U.S. - Lirkki, Roni; Taipale, Aatu (2025)
Real estate investing is divided into direct and indirect real estate investment, in which the first investor itself controls mostly residential or office property. Indirect real estate investment is performed via financial instruments, such as acquiring shares in stocks or indices. The unifying factor for both forms of investment is real estate’s diversification benefits.